Tasaluh Sebagai Metode Pembagian Waris Perspektif Hukum Progresif - Khotifatul Defi Nofitasari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The distribution of inheritance must be carried out in accordance with Sharia, as explicitly regulated in the Qur'an and Hadith. According to most scholars, the provisions found in the Qur'an and Sunnah, which provide clear guidance, are considered Qat’i (definitive). However, Muslims tend to prefer reconciliation or consultation (musyawarah) in inheritance distribution. This practice is not only a common custom in society but is also regulated in Article 183 of the Compilation of Islamic Law (KHI), which explains that tasaluh is a method in which an heir waives their inheritance rights to be given to other heirs. This research is library-based, using qualitative data, and follows a descriptive-analytical approach. The goal is to describe the tasaluh method of inheritance distribution from the perspectives of both Islamic law and the Compilation of Islamic Law, and then analyze it through the lens of progressive law. The study uses a normative approach to examine tasaluh in inheritance distribution via progressive legal theory. The findings suggest that inheritance distribution through peaceful methods, such as takharruj in Islamic law, can be seen as an implementation of progressive law, which prioritizes humanity and social justice. By encouraging deliberation and mutual agreement, this method accommodates social needs and family harmony. This approach shows that law need not be rigid; it should provide solutions that promote societal welfare. Therefore, Islamic law, through peaceful inheritance distribution, offers fairness and justice, aligned with progressive law principles.